Sex Offenders—America's New Witches? A Theoretical Analysis of the Emergence of Sex Crime Laws. Issue 4 (2nd April 2016) - Mancini, Christina; Mears, Daniel P.
ABSTRACT: During the 1990s, the United States enacted several punitive sex crime laws. Contemporary scholarship suggests this shift can be understood as a modern "witch hunt." However, theoretical accounts have yet to examine systematically the emergence of such legislation. This study applies two theories—the first by Erikson and the second by Jensen—to assess whether they accord with known facts about the proliferation of these laws. Broad support for the theories as accounts for the punitive trend in sex crime legislation exists, but the inclusion of information dissemination as an additional factor would strengthen these accounts. Implications are discussed.